On the Marginal Functions and Features of Object Clitics, with Special Reference to Modern Greek - Bibis, Nick (Revue québécoise de linguistique)

(untitled) (Université du Québec à Montréal, 2000)
ABSTRACTWritten within the minimalist program approach to grammar (Chomsky 1995), this paper examines the nature of θ-role requirements in three types of object clitic constructions: idiomatic and affected accusative in Modern Greek, and affected dative in Modern Greek and French. I do not treat the idiomatic clitic constructions as lexically listed VPs, but as being derived syntactically. Furthermore, I argue that these constructions contain Tense and Person intrinsic features that are not visible to the syntax, and an obligatory θ-feature [EXPERIENCER] checked in the syntax by means of the operation Attract-F. Affected accusatives are analyzed as non-A-bound θ-marked affixes which attract an interpretable θ-feature [EXPERIENCER] associated with V. A simple VP syntactic structure without clitic movement is attributed to them. Lastly, for affected dative constructions, I propose a v shell syntactic structure with base-generation of the clitic.